ANALISIS TINGKAT KERAWANAN PERGERAKAN TANAH DI KELURAHAN TAAS KECAMATAN TIKALA KOTA MANADO, SULAWESI UTARA - Kasenda, C.; Budiharso, A.S. (LPPM Universitas PRISMA, 2024)
Disasters are events that can harm affected communities, caused by natural, non-natural, or human factors. Several dominant factors contributing to vulnerability to landslides or soil movements include rainfall intensity, slope steepness, soil type, as well as geological and geomorphological conditions. Taas District, as the study area, exhibits potential landslide hazards that require assessment. This research utilizes assessment methods and leverages Geographic Information System (GIS) tools. The study results, based on classification according to Minister of Public Works Regulation No. 22/PRT/M/2007, indicate low and moderate landslide vulnerability classes within the research area. These findings provide valuable insights for further mitigation efforts.